Real-world national trends and socio-economic factors preference of sodium-glucose cotransporter-2 inhibitors and glucagon-like peptide-1 receptor agonists in China - Li, Cao; Guo, Shanshan; Huo, Jiping; Gao, Yiming; Yan, Yilong; Zhao, Zhigang (Frontiers in Endocrinology, 2022)
Backgrounds Robust evidence have demonstrated the beneficial effect of Sodium-glucose cotransporter-2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1RA) in T2D patients with cardiovascular diseases and chronic kidney disease. Multiple studies analyzed patterns and predictors of SGLT2i and GLP-1RA in the US, Europe and worldwide. However, there is no study about the utilization of these two classes of drugs in real-world in China. Method A total of 181743 prescriptions of SGLT2i and 59720 GLP-1RA were retrospectively pooled from Hospital Prescription Analysis Cooperation Project from 2018 to 2021. The social-economic characteristics of patients and prescribers, including age, gender, residency, hospital level, insurance type, department visited, and payment amount, were collected and analyzed to study trends and risk factors associated with preference among two antidiabetics. Results Annual number of prescriptions of SGLT2i significantly increased to approximately 140 folds, while GLP-1RA increased to about 6.5 folds. After adjustment for socio-economic information, several patients or physician characteristics were positively associated with the preference of GLP-1RA, including female gender (OR 1.581, 95% CI 1.528-1.635), residents in second-tier cities (OR 1.194, 95% CI 1.148-1.142), visiting primary or secondary hospital level (OR 2.387, 95% CI 2.268-2.512); while other factors were associated with the preference of SGLT2i, including older adults (OR 0.713, 95% CI 0.688-0.739), uncovered by insurance (OR 0.310, 95% CI 0.293-0.329), visiting other departments compared with endocrinology. In addition, the share of SGLT2i and GLP-1RA was low but in an increasing tendency. Conclusions SGLT2i and GLP-1RA prescription significantly increased from 2018 to 2021. The socio-economic risk factors in choosing SGLT2i or GLP-1RA highlight an effort required to reduce disparities and improve health outcomes.